Physical performance determinants in competitive youth swimmers: a systematic review - Price, T.; Cimadoro, G.; Legg, S. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Youth swimming performance is determined by several physiological, biomechanical and anthropometric characteristics. This review aimed to identify physical performance determinants of youth swimming performance, assessing strength, power, anaerobic, aerobic and body composition measures.